2014
DOI: 10.3390/ijms151017411
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Function and Clinical Utilization of CD147 in Human Diseases: A Review of the Current Scientific Literature

Abstract: CD147 or EMMPRIN is a member of the immunoglobulin superfamily in humans. It is widely expressed in human tumors and plays a central role in the progression of many cancers by stimulating the secretion of matrix metalloproteinases (MMPs) and cytokines. CD147 regulates cell proliferation, apoptosis, and tumor cell migration, metastasis and differentiation, especially under hypoxic conditions. CD147 is also important to many organ systems. This review will provide a detailed overview of the discovery, characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
201
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(205 citation statements)
references
References 175 publications
(256 reference statements)
3
201
0
1
Order By: Relevance
“…Moreover, knockdown of CD147 and CD98 with siRNA by electroporation had an antiproliferative effect and use of lipid-based transfection reagents, such as DMRIE-C or oligofectamine, yielded low transfection efficiency in suspension nonadherent B cell lines (data not shown). The antiproliferative effect of CD147 knockdown has been previously reported and reviewed (64,65). In addition, the m.w.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, knockdown of CD147 and CD98 with siRNA by electroporation had an antiproliferative effect and use of lipid-based transfection reagents, such as DMRIE-C or oligofectamine, yielded low transfection efficiency in suspension nonadherent B cell lines (data not shown). The antiproliferative effect of CD147 knockdown has been previously reported and reviewed (64,65). In addition, the m.w.…”
Section: Discussionmentioning
confidence: 94%
“…+ taMP and CD147 + EpCAM -MPs were at day 7 post-OP in median not differing compared to respective pre-OP values ( Figure 4C-4D). We speculate that CD147 + EpCAM − MPs were shed from fibroblast, T-cells, stroma cells, epithelial cells during tumour resection indicating tissue remodelling, migration and cancer cell invasion in which EMMPRIN/CD147 might play role as suggested by others [7,20,21].Taken together, in vivo cancer cells shed distinct taMP populations with a unique pan-cancer MPs-based signature. Even if each tumour is composed of a mixture of heterogeneous tumour cells, the released EpCAM + and EpCAM + CD147 + taMPs can be reliable detected in the circulation in both primary and metastatic tumour-bearing patients ( Figure 4E).…”
mentioning
confidence: 82%
“…+ taMP and CD147 + EpCAM -MPs were at day 7 post-OP in median not differing compared to respective pre-OP values ( Figure 4C-4D). We speculate that CD147 + EpCAM − MPs were shed from fibroblast, T-cells, stroma cells, epithelial cells during tumour resection indicating tissue remodelling, migration and cancer cell invasion in which EMMPRIN/CD147 might play role as suggested by others [7,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…EMMPRIN mainly participates in the adhesion between cells or ground substances in a pathological state, such as in a malignant tumor. In vitro studies showed that EMMPRIN from tumor cells can stimulate human fibroblasts and endotheliocyte to secrete MMP and thus participate in the destruction of the natural tissue mechanical barrier to help tumor cell invasion and diffusion (Xiong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%